THE APPLICATION OF REFLECTANCE SPECTROSCOPY AND GEOCHEMICAL ANALYSIS METHODS IN CHARACTERIZATION OF RARE EARTH ELEMENTS (REES) IN CLAY MINERALS - Aditya S. N., Andreyan
The Schwaner Mountains in West Kalimantan have several granite plutons that may contain REE (rare earth elements) minerals such as monazite, xenotime, apatite, allanite, and titanite. Granite weathering can produce REE ion-adsorption type minerals in the regolith. These adsorption-type REE minerals are clay minerals that absorb 3+ ions. The characteristics of these clay minerals can be identified through their wave patterns using wave interpretation methods after sampling and analyzing in powdered form with a Spectral Analysis Device (ASD). The enrichment patterns and wave characteristics of each horizon will be observed in this study. Xray Diffraction (XRD), X-ray Fluorescence (XRF), Inductively Coupled Plasma Mass Spectrometry (ICP-MS), and reflectance spectroscopy methods are used to understand the characteristics of REE in the weathered granite of Granit Laur. The tests classified the granite as peraluminous granodiorite. XRD and ASD tests identified REE-bearing minerals such as monazite and allanite, and clay minerals binding REE-ion adsorption 3+, such as kaolinite. ASD could capture the wave patterns of clay minerals but could not capture REE waves due to interference from iron ions in the sample. ICP-MS showed that the concentration of REE in the clay sample is lower than in the parent rock. The concentration of REE decreases from the original rock to the weathered layer because kaolinite is the only weathered mineral present, which is where REE ions attach to the mineral's surface.